A Dynamic Thermodynamic Resolution Strategy for the Stereocontrolled Synthesis of Streptonigrin. (7th December 2022) - Valdez Pérez, Luis F.; Bachollet, Sylvestre P. J. T.; Orlov, Nikolai V.; Kopf, Kenji P. M.; Harrity, Joseph P. A.
Abstract: We report that axially chiral biaryl boronic esters can be generated with control of atroposelectivity by a Binol‐mediated dynamic thermodynamic resolution process. These intermediates can be progressed to enantioenriched products through stereoretentive functionalization of the carbon–boron bond. Finally, we have exploited this method in the first highly stereoselective total synthesis of P ‐streptonigrin. Abstract : The long‐standing challenge of preparing P ‐streptonigrin with high levels of enantioenrichment has been addressed by the use of an atroposelective dynamic thermodynamic resolution process. The strategy highlights the versatility of organoboron chemistry, as it plays a central role in ring synthesis, atropisomer resolution and functional group installation.